Penyebaran Metode Tadarus Al-Qur’an Harfiyah Karya K.H. Udung Abdurrahman Ya’kub di Kabupaten Bandung (1930-1992) - Suni Mutmainah (UIN Sunan Gunung Djati Bandung, 2025)
This article explores the historical spread of the harfiyah Qur'anic recitation method developed by K.H. Udung Abdurrahman Ya’kub from Pesantren Cikoneng to various regions in Bandung Regency between 1930 and 1992. The method is known for its literal approach to understanding the Holy Qur’an in Sundanese. The article also highlights the role of the Islamic Boarding School Foundation (YPI), the Islamic Union (SI), and educational institutions in developing and preserving this method in areas such as Soreang, Majalaya, and Arjasari.